Order in Early Chinese Excavated Texts Natural, Supernatural, and Legal Approaches - Wang, Zhongjiang; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Recently discovered ancient silk and bamboo manuscripts have reformulated our understanding of ancient Chinese thought. They show that ancient Chinese philosophy was and is much richer and more complex than we ever imagined, and they chart the path from belief in powerful spirits and gods to the discovery of universal laws and order.
Keywords: History; Asia -- History; China -- History; Oriental literature; Philosophy; Languages; Language and languages; Translation and interpretation; History; Asian History; Translation; History of Philosophy; Asian Literature; Asian Languages; History of China; Electronic books